TINDAK PIDANA PEMERKOSAAN TERHADAP SEORANG WANITA DALAM KEADAAN TIDAK BERDAYA: Crime of Rape Against a Woman in a State of Helplessness - Wibisono, Yusuf; Susetyo, Heru (Faculty of Law, Universitas Trisakti, 2024)
Currently, the crime of rape is rampant and has received considerable attention from the public. The crime of rape often brings difficulties, both in the stage of investigation, prosecution, and at the stage of imposing a verdict during the settlement of the case. Rape is an act in which a person commits violence or threat of violence to force a woman who is not his wife to have sex with him, as in the case of Decision Number 390/Pid.B/2021/PN Smn, the unnamed perpetrator committed the crime of rape against awoman who was in a state of helplessness or unconsciousness whose punishment was imposed based on Article 285 of the Criminal Code, The main problem is how the crime of rape in theory and its regulationin Indonesia, and whether the application of Article 285 of the Criminal Code to the perpetrator of rape against a woman in a helpless state is appropriate. This research is a normative research that is descriptive analysis, and the data used is secondary data, and data collection is done by literature study.The results concluded that the perpetrator's actions were a type of